Respuesta :
Answer:
[tex]a_{n}[/tex] = - 6n + 4
Step-by-step explanation:
Note there is a common difference d between consecutive terms of the sequence, that is
d = - 8 - (- 2) = - 14 - (- 8) = - 20 - (- 14) = - 26 - (- 20) = - 6
This indicates the sequence is arithmetic with n th term
[tex]a_{n}[/tex] = a₁ + (n - 1)d
Where a₁ is the first term and d the common difference
Here a₁ = - 2 and d = - 6, thus
[tex]a_{n}[/tex] = - 2 - 6(n - 1) = - 2 - 6n + 6 = - 6n + 4
Answer: there is no need to write a formula
Step-by-step explanation: this are just integers apply the operations you will get the answer .